Evaluating diagnostic value of clinical symptoms and signs for chronic sinusitis by CT-scan in patients admitted to Ardabil city hospital, Iran - Fouladvand, Tirzad; Pirzadeh, Akbar; Isazadehfar, Khatereh; Alipour, Alireza (International Journal of Advances in Medicine, 2019)
Background: Chronic rhinosinusitis (CRS) refers to inflammatory nasal and para nasal sinuses which last at least 12 weeks. Despite its high prevalence, it is not easy to diagnose, and clinical criteria and simple radiographs are not so sensitive. The aim of this study was to investigate the diagnostic value of clinical symptoms and signs for chronic sinusitis by Ct-scan in patients admitted to Ardabil city hospital, Iran. Methods: This descriptive cross-sectional study has been done on 83 patients with CRS symptoms who referred to ENT of Ardabil city hospital. The necessary checklist included information such as age, gender, clinical symptoms and CT scan findings were completed and analyzed by statistical methods in SPSS version 21. Results: Of all 83 patients, 55.4% were female and most of patients were in age group 30-39 years with 30.1%. Of all patients, 29 (35%) had positive findings in CT scan of which 72.4% were female. The highest rate of sinus involvement was in the ethmoid sinus. The highest positive predicted value was for nose congestion with OR=2.26 and the lowest was for facial pain and toothache each with OR=0.1. Conclusions: In general, clinical symptoms have a small predictive value in the diagnosis of sinusitis and should be evaluated with CT scan findings (15.7%).